A gestão pedagógica do programa mais educação: um olhar a partir da experiência da escola Teodora Bentes - SANTOS, Áurea Andrezza Silva dos (Universidade Federal do Pará, 2013)
With the reduced role of the state and the adoption of neoliberal policies in the areas of social policy such as education, see the precariousness of the quality of public education in Brazil. Some plans made in recent decades seeking to address this problem. The most recent Development Plan of Education (PDE) (in force since 2007) has several goals that aims to improve the quality of teaching in basic education in Brazil. Among the various actions of this plan, we select the More Education Program (SMEs), whose goal is the integral education, which began to be implemented in Brazilian public schools from 2008. Focusing on the public policy context this study deals with the management of this educational program and its relationship with indicators of learning: a look from the experience of Teodora Bentes School between the years 2008 and 2012. The research is a qualitative methodological ways to approach the historical and dialectical materialism, with the technical analysis literature and documents, and the instrument that will be conducted semistructured interviews with education professionals who work in the school as director, program coordinator, the education specialist and teachers beyond the analysis of indicators of learning through the bulletins of a group of school students who attend the SMEs from the start of their deployment in School Teodora Bentes. The first chapter is the understanding of social policies and their implications for educational policies these policies are developed through social programs scaled down public school. The second chapter presents a brief review of its historical development Integral Education in Brazilian education, its concept and characterization and theoretical foundation of the development of SMEs in the same school. The third chapter deals with the data from the study on the program developed at the School Teodora Bentes. Becomes relevant in our research seek to contribute to the academy and schools on comprehensive education to be a topic little explored and the search for a greater understanding of the More Education Program.